PELAKSANAAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM TERHADAP PEMBANGUNAN JEMBATAN LALOVE KOTA PALU - Pakki, Darwat; Citra Dewi, Marini (Maleo Law Journal, 2022)
Land is the most important and inseparable part of human life, especially for the community. On land that is occupied by the community, the community can take the results, utilize and also build buildings/buildings according to their designation. For land rights holders, the issue of compensation is the most complicated central issue to deal with in land acquisition efforts. It is often forgotten that interpretation as a social function also implies that land rights must be used according to their nature and purpose, so that they can benefit the land rights owners and the community. One of the land acquisitions that have been carried out by the Regional Government of Palu City, namely the Construction of Bridge V or also called the Lalove Bridge which for the people of the city of Palu in addition to being a public facility for the community in terms of transportation, the construction of the Lalove bridge is also a magnet for community tourism. Like exercising, gathering with family to enjoy the afternoon. Based on the reality that exists in the community, there are still incidents of land rights holders, late and or not replacing losses that make the community restless. So this can cause problems regarding land acquisition, especially the construction of the Lalove bridge in Palu City.